2003
DOI: 10.1002/jnr.10686
|View full text |Cite
|
Sign up to set email alerts
|

Role of phosphatidylinositol 3‐kinase in neuronal survival and axonal outgrowth of adult mouse dorsal root ganglia explants

Abstract: Adult ganglionic peripheral neurons have lost dependence on target-derived neurotrophin signaling for survival and regeneration after injury. To understand the mechanisms required to sustain such processes at maturity, we are studying neuronal survival and axonal outgrowth of adult mouse dorsal root ganglia (DRG) explants. We have here examined the role of phosphatidylinositol 3-kinase (PI3-K) activity. Both neuronal survival and axonal outgrowth of spontaneously growing preparations were decreased significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(36 citation statements)
references
References 55 publications
3
32
1
Order By: Relevance
“…Pezet et al [25] reported that very low p-Akt levels were present in 'almost all neurons' in the rat. This is in agreement with the in vitro study in the mouse by Edström and Ekström [58] , reporting that most neurons from freshly dissected DRGs are p-Akt-IR, whereas other cell types, such as satellite cells, were negative. Zhuang et al [24] and Xu et al [26] found that ϳ 10% of rat DRG neurons are pAkt positive, versus our 50% in the mouse.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Pezet et al [25] reported that very low p-Akt levels were present in 'almost all neurons' in the rat. This is in agreement with the in vitro study in the mouse by Edström and Ekström [58] , reporting that most neurons from freshly dissected DRGs are p-Akt-IR, whereas other cell types, such as satellite cells, were negative. Zhuang et al [24] and Xu et al [26] found that ϳ 10% of rat DRG neurons are pAkt positive, versus our 50% in the mouse.…”
Section: Discussionsupporting
confidence: 81%
“…Our findings also seem to contrast the marked decrease in pAkt after 24 h in mouse DRG cultures, where all neurons, of course, have been axotomized, an effect which, however, was recorded very early, just after 24 h in culture [58] . So the differences could be explained by different experimental models and/or species differences.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Activated Akt is released from the cell membrane into the cytoplasm or nucleus to further transmit the signals and execute its biological functions. Thus, Akt phosphorylation can be used as an indicator of PI3K activity [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…PI3-kinase has been shown to be involved in neurite outgrowth signaling (Rodgers and Theibert, 2002), especially in axonal formation (Edström and Ekström, 2003;Ménager et al, 2004). On the other hand, teneurin-2 is a type II transmembrane protein (Otaki and Firestein, 1999), and is involved in the formation of filopodia, and growth cone enlargement (Rubin et al, 1999).…”
Section: Discussionmentioning
confidence: 99%